Pediatric Retinal Diseases - Chan, R. V. Paul.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This volume on pediatric retina covers all aspects of pediatric retinal diseases as their understanding, diagnosis and management is still under evolution and a challenging task. Newer diagnostic and surgical techniques are being developed and are being adapted for better visual outcome in pediatric cases. It comprises of 10 chapters describing the medical and surgical aspects. The text and figures have been provided in a lucid manner to enhance the understanding of the reader. This volume covers OCT angiography for pediatric retinal disease, clinical spectrum of retinopathy of prematurity, which has become an ever increasing burden of disease for the society and needs special attention, anti-VEGF for retinopathy of prematurity, surgical management of retinopathy of prematurity, retinopathy of prematurity: atypical aspects, Coats$1 (Bdisease, pediatric retinal inflammatory disorders, congenital X-linked retinoschisis, familial exudative vitreoretinopathy, hematologic disorders: leukemia, hyperviscosity, anemia. It provides descriptions of these disease accompanied by numerous helpful images to highlight these conditions. This atlas will assist the vitreoretinal specialists, general ophthalmologists, retina fellows and post graduate students in successfully identifying the key features of these challenging pediatric vitreoretinopathies. Pediatric Retinal Diseases is one of the nine volumes of the series Retina Atlas. This series provides global perspective on vitreoretinal diseases, covering imaging basics, retinal vascular disease, ocular inflammatory disease, retinal degeneration, surgical retina, ocular oncology, pediatric retina and trauma. Retina Atlas is spread over 9 volumes and about 100 chapters, covering validated and comprehensive information on retinal disorders.s
OCT Angiography for pediatric retinal disease -- Clinical Spectrum of Retinopathy of Prematurity -- Anti-VEGF for Retinopathy of Prematurity -- Surgical Management of Retinopathy of Prematurity -- Retinopathy of Prematurity: Atypical Aspects -- Persistent Fetal Vasculature -- Familial Exudative Vitreoretinopathy -- Coats$1 (BDisease -- Pediatric Retinal Inflammatory disorders -- Congenital X-Linked Retinoschisis -- Hematologic Disorders: Leukemia, Hyperviscosity, Anemia.s
Keywords: Ophthalmology; Ophthalmology; Retinal Diseases; Child